Author's Guide to Journals in Library & Information Science - Norman D., Stevens (Routledge, 2020)
This book, first published in 1982, focuses on providing information about the policies and practices surrounding the preparation and submitting of articles to the major journals in library and information science. This guide includes all the major American, Canadian, British, and international professional journals that solicit, accept and publish articles in the field.